2016
DOI: 10.1159/000443986
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Monotherapy in a Patient with Unresectable Hepatic Epithelioid Hemangioendothelioma

Abstract: A 49-year-old Japanese man had multiple huge masses (max. size 60 mm diameter) in his liver. These tumors were pathologically diagnosed by tumor biopsy as epithelioid hemangioendotheliomas of the liver. In this case, multiple liver tumors existed in both lobes. Also this patient did not agree to receive surgical resection including liver transplantation. Chemotherapy with sorafenib at a dose of 400 mg/body twice a day was started. About 6 months later, CT findings revealed that these tumors were shrinking slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Additional treatment after LT may be necessary for advanced HEH, such as the cases with vascular invasion. Successful treatment with chemotherapy has been reported, using sorafenib and thalidomide, doxorubicin, cyclophosphamide, and interferon . However, all reports have a small number of cases, and the effect as an established adjuvant therapy after surgery is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional treatment after LT may be necessary for advanced HEH, such as the cases with vascular invasion. Successful treatment with chemotherapy has been reported, using sorafenib and thalidomide, doxorubicin, cyclophosphamide, and interferon . However, all reports have a small number of cases, and the effect as an established adjuvant therapy after surgery is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular or combined macro-microvascular invasion have been reported as prognostic factors, and the pre-LT waiting time (120 days or less) and hilar lymph node invasion were reported as risk factors for recurrence after LT. 16 Additional treatment after LT may be necessary for advanced HEH, such as the cases with vascular invasion. Successful treatment with chemotherapy has been reported, using sorafenib 17,18 and thalidomide, 19 doxorubicin, 20 cyclophosphamide, 21 and interferon. 22 However, all reports have a small number of cases, and the effect as an established adjuvant therapy after surgery is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the use of sorafenib took more advantages over other anti-angiogenic agents because of its dual anti-tumor activity. [20] In a case report, Kobayashi et al [21] used sorafenib monotherapy in a patient with mutiple unresectable lesions, who did not agree to receive surgical resection including liver transplantation. About 6 months later, CT findings indicated that these tumors were shrinking slightly; even 60 months later, the partial response was still observed with sorafenib monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Durable stabilization was also observed in sorafenib therapy, with partial response for 5 years and stable disease in almost 2 years being observed in previous reports. [ 68 , 69 ] In a phase 2 study of progressive EHE patients treated with sorafenib, the 2-, 4-, 6-, and 9-month progression-free survival was 84.6% (11 of 13), 46.4% (6 of 13), 38.4% (5 of 13), and 30.7% (4 of 13), respectively. [ 70 ] In contrast, only 3 EHE patients who were treated with sunitinib have been previously reported, with stabilization lasting about 10 months, 2 years, and 6 years, respectively.…”
Section: Discussionmentioning
confidence: 99%